The Analysis of Growth And Survival Rate of Carp (Cyprinus Carpio) Rearing With Addition of Water Hyacinth Flour (Eichornia Crassipes) As an Artificial Feed - Utomo, Munzir; Rais, Muhammad; Kaseng, Ernawati Syahruddin (Journal of Agroscience Indonesia, 2023)
This research was an experimental study aiming to determine the effect of difference in commercial feed and artificial feed with the addition of water hyacinth (Eichornia crassipes) flour. There were 6 experimental units which included 2 treatments and 3 replications, the measured parameters were growth which includes absolute weight growth, absolute length growth and specific growth rate, survival rate and feed efficiency which includes feed conversion ratio, feed utilization efficiency and protein conversion ratio. Water quality parameters, including ammonia, pH and temperature were also measured in this study. The research data were analyzed using the t test data analysis method. The results showed that the feeding of commercial feed and the artificial feed with the addition of water hyacinth flour did not have a significantly different effect on growth parameters, survival rate, feed efficiency and water quality (p>0.05). The best treatment was produced by the artificial feeding treatment with addition of water hyacinth flour on growth and feed efficiency parameters but produced a lower result on survival rate compared to the commercial feeding treatment. In conclution, the artificial feed with addition of water hyacinth flour could be used as an alternative feed to reduce the cost of fish feed cost during aquaculture.